Lithuanian Literary Magazine Kulturos barai –Cultural Mission in a Modern Way (Libellarium: journal for research in the field of information and related sciences, 2018)
The aim of this article is to present shortly the regulations and aims of Lithuaniaʼs cultural policy concerning cultural publications, to introduce publishing models of one of the biggest and most important Lithuanian literary publications Kulturos baraiand to discuss its importance for the Lithuanian literary society. For a small country, culture is one of the most important features of its identity and that is why we need to recognize the enduring value and mission of literary media – to inform about literary life, to influence public taste, to be an active part of culture, a tool for societal education, and the space in which creators can express themselves. On the other hand, increasing globalization and changing society needs may raise a question if literary publications perform their mission in a modern way, if culture is not equaled to a narrower art concept. Kulturos baraiis one of more than 20 Lithuanian literary periodicals with long tradition. Started in 1965 as an amateur publication, thanks to influential authors the magazine turned into a publication which is intended to shape the cultural strategy. In 1988, public discussion events organized by Kulturos baraigave an impetus to create the Reform Movement in Lithuania. At that time the whole cultural situation was changing in Lithuania – when Reform Movement was established, culture started to be understood as the basis for identity, and literary publications became the space which assisted to return memory. Literary pages were unprofitable for the mass media which had just been born, however, they were important as a sign of prestige. Kulturos barai, having played an important role in shaping the cultural taste in society several decades ago, still remains one of the most progressive and most modern literary publications, which performs its content management and dissemination organization in the best possible way. The research is based on the interview with an editor-in-chief of the magazine Kulturos barai.
Keywords: literary periodicals; Kulturos barai; publishing; Lithuania; cultural policy